1998
DOI: 10.1183/09031936.98.11051188
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial stenosis and sclerosing mediastinitis: an uncommon complication of external thoracic radiotherapy

Abstract: aaThoracic radiotherapy is one of the major treatment modalities in lung cancer. Radiation pneumonitis and fibrosis are well-known side-effects. ''Radiation bronchitis" in the form of inflammatory reaction of the airways mucosa following therapeutic external-beam radiation and highdose endobronchial radiation (brachytherapy) has also been reported. Otherwise, there is very little mention in the literature regarding the effects of the radiation on the airways.In this article, we report a case of sclerosing medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 7 publications
0
19
0
1
Order By: Relevance
“…Sclerosing mediastinitis was first described by Hallet in 1948 [3] and many similar case reports followed [1,2,4,5,6,7,8,9,10,11,12]. Recently, Rossi et al [9] reviewed the current understanding of sclerosing mediastinitis and indicated the clinical manifestations that might allow us to suspect this disorder.…”
Section: Discussionmentioning
confidence: 96%
“…Sclerosing mediastinitis was first described by Hallet in 1948 [3] and many similar case reports followed [1,2,4,5,6,7,8,9,10,11,12]. Recently, Rossi et al [9] reviewed the current understanding of sclerosing mediastinitis and indicated the clinical manifestations that might allow us to suspect this disorder.…”
Section: Discussionmentioning
confidence: 96%
“…Other diseases that have been associated with fibrosing mediastinitis include autoimmune disease, Behçet disease, rheumatic fever and other idiopathic fibro-inflammatory disorders such as retroperitoneal fibrosis, sclerosing cholangitis, Riedel thyroiditis, and pseudotumor of the orbit [6,7,10,11]. Trauma, radiation, methysergide maleate have also been associated with the development of fibrosing mediastinitis [5,6,12] Idiopathic cases are more often of the diffuse type while post inflammatory cases are more frequently localised [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although the cause and pathogenesis remain unknown, granulomatous diseases (e.g., histoplasmosis, tuberculosis, sarcoidosis), radiation therapy and drugs (methysergide) are the most common causes. An idiopathic form has also been described [4].…”
Section: Introductionmentioning
confidence: 96%